Features of managing the parameters of construction projects using precast concrete - BLONNY, Andrey; ZINKOV, Oleg (Ways to Improve Construction Efficiency, 2025)
The article provides for the consideration and definition of the methodological basis for determining the time parameters of the delivery of reinforced concrete structures at the stage of the current implementation of a construction and investment project in conditions of external changes. Known optimization methods for reducing the construction period of complex development objects with precast concrete involve the use of parallel methods on two or more technologically similar works with an increased flow reduction period. In the areas of scientific research, examples of balancing installation work by using special and universal machines with specialized specialists or complex teams were given, and technical and economic indicators were determined for the optimization performed. When considering construction projects by customers - investors of construction projects, they usually consider a traditional approach to investment design, where the investment and construction project is considered as "an object of a financial transaction, which is associated with the distribution of financial receipts and expenditures over time". Accordingly, the essence of investment design within the framework of traditional practice is reduced to the projection of logistical flows of the construction of the facility into the future for the duration of the investment period and the total construction period. The use of precast concrete in construction projects leads to increased time and cost efficiency. The production procedure takes place at a distance from the facility, which allows for simultaneous execution of tasks and minimizes the duration of construction work on site. As a result, the completion of projects is accelerated and labor costs are reduced. The purpose of the article is to further study the essence of the impact of the external nature of the investment and construction project, both technological and financial, and the impact of risk on determining the effectiveness of the investment project, regarding the use of precast concrete building structures and structures to manage the risks of implementing investment and construction projects. The achievement of this goal must be considered in relation to decision-making under conditions of uncertainty regarding the time parameters of the project and the projected risk of production costs.